Determinants of Academic Achievement in Introductory Physics Courses among Distance Learners - Folashade Afolabi (PJDOL, 2019)
Teaching quantitative courses in open and distance learning (ODL) has been a challenge to educators. This research work examined factors that determined the academic achievement of distance learners in introductory physics. A questionnaire consisted of twenty-five (25) items was used to collect data from one hundred (100) respondents who were selected using random sampling technique. The result showed that use of technology and technology components were rated high in determining the academic achievement of distance learners. However, the variables examined could be improved upon by incorporating more factors.